Strategi Penerapan Kurikulum Pendidikan Agama Islam Berbasis Moderasi Beragama dalam Membentuk Peserta Didik Moderat: Systematic Literatur Review - Havida, Nadhiva Iffany; Mukharomah, Awwalina (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2025)
The emergence of various findings and indications regarding the entry of radical ideas in the education sector has become a concern. Efforts to strengthen and develop an Islamic education curriculum that emphasizes moderation values are needed to overcome this issue. This study aims to identify effective strategies in implementing an integrated Islamic Religious Education (PAI) curriculum for religious moderation in schools. This type of research uses the Systematic literature review method. This research utilizes Garba Rujukan Digital (Garuda), a repository of Indonesian scientific articles, as a data source. In this study, the author analyzed 9 articles with inclusion criteria written in Indonesian and published in the time span of 2014-2024. The article search strategy used keywords; curriculum, Islamic religious education and religious moderation. This research uses content analysis techniques in analyzing the results of the research data that has been collected. The results revealed that the process of implementing an Islamic religious education curriculum integrated with the concept of religious moderation has four strategies that must be implemented in realizing moderate students, namely; curriculum with religious moderation, educators, materials, methods, and evaluation. This research also reveals that evaluation needs to be done at the stage of using digital media in increasing religious moderation in students.